GAMBARAN NILAI PAKAI DAN NILAI INVESTASI OBAT MENGGUNAKAN METODE ABC DI APOTEK TELUK ARTA MEDIKA PERIODE JANUARI 2020-DESEMBER 2020 - Novita Herrawati; Dedy Frianto; Surya Amal (Jurnal Buana Farma, 2022)
Inventory control is very important in a company, because the company's physical inventory involves the largest investment in current assets. As well as planning and management of drugs that are not good will cause drug accumulation and drug stock vacancies, ABC (Pareto) analysis is carried out. ABC (Pareto) analysis is an analysis based on the economic value of goods. In this ABC value analysis, it can be identified the types of drugs that require the most costs. The purpose of this study was to determine the use value and investment value of drugs using the ABC method at Teluk Arta Medika Pharmacy. This study uses a non-experimental type of research where the required data is already available without any manipulation process. Data was obtained from data on drug use at the Teluk Arta Medika Pharmacy during January to December 2020 using quantitative data. By using ABC analysis, the results of this study indicate that there are four periods of drug use and investment in one year and each period consists of three months of use as many as 292,416 pcs which are included in group A and have an investment value of Rp. 2,217,463,364. In group B, there are 84,896 pcs of usage with an investment of Rp. 639,566,963 while in group C there are 42,061 pcs of use with an investment of Rp. 318,451,574. Keywords: ABC Method, Medicine, Pharmacy